The Effect of Blended Problem-Based Learning on Strengthening Islamic Character Values: A Meta-Analysis of Islamic Education Studies - Wahono Wahono; Sholehuddin Sholehuddin; Burhan Efendi; Tomi Apra Santosa; Anwar Manahor (AL-ISHLAH: Jurnal Pendidikan, 2025)
Islamic character education is a critical component of Islamic Religious Education (IRE), aiming to cultivate values such as honesty, responsibility, and social concern. In response to the challenges of modern education, Blended Problem-Based Learning (Blended-PBL) is proposed as an innovative approach to foster these values among students. This study employs a meta-analysis approach to examine the effect of Blended-PBL on strengthening Islamic character values in students. A systematic literature search was conducted across ERIC, Scopus, Wiley, and Google Scholar databases for studies published between 2020 and 2025. Of 119 articles identified, 10 met the inclusion criteria. Data were analyzed using the JASP software, applying a random-effects model to calculate pooled effect sizes and assess heterogeneity and publication bias. The analysis revealed a significant positive effect of Blended-PBL on strengthening Islamic character values (pooled effect size = 0.692; t = 6.403; p 0.001), with moderate to high effect sizes across studies. The heterogeneity test indicated variation among studies (Q = 29.124; p 0.001), justifying the use of a random-effects model. Egger’s test showed no evidence of publication bias (p = 0.078). Findings suggest that Blended-PBL is an effective pedagogical model in IRE contexts, supporting not only cognitive development but also character formation. This model integrates reflective, contextual learning with digital flexibility, offering practical implications for value-based Islamic education in higher institutions.